Topical Anti-Inflammatory Effects of Isorhamnetin Glycosides Isolated from Opuntia ficus-indica. (2nd March 2015) - Antunes-Ricardo, Marilena; Gutiérrez-Uribe, Janet A.; Martínez-Vitela, Carlos; Serna-Saldívar, Sergio O.
Abstract : Opuntia ficus-indica (OFI) has been widely used in Mexico as a food and for the treatment of different health disorders such as inflammation and skin aging. Its biological properties have been attributed to different phytochemicals such as the isorhamnetin glycosides which are the most abundant flavonoids. Moreover, these compounds are considered a chemotaxonomic characteristic of OFI species. The aim of this study was to evaluate the effect of OFI extract and its isorhamnetin glycosides on different inflammatory markers in vitro and in vivo . OFI extract was obtained by alkaline hydrolysis of OFI cladodes powder and pure compounds were obtained by preparative chromatography. Nitric oxide (NO), cyclooxygenase-2 (COX-2), tumor necrosis factor- (TNF-) α, and interleukin- (IL-) 6 production were measured. NO production was tested in lipopolysaccharide-stimulated RAW 264.7 cells while in vivo studies were carried on croton oil-induced ear edema model. OFI extract and diglycoside isorhamnetin-glucosyl-rhamnoside (IGR) at 125 ng/mL suppressed the NO production in vitro (73.5  ±  4.8 % and 68.7 ± 5.0 %, resp.) without affecting cell viability. Likewise, IGR inhibited the ear edema (77.4 ± 5.7 %) equating the indomethacin effects (69.5 ± 5.3 %). Both IGR and OFI extract significantly inhibited the COX-2, TNF- α, and IL-6 production. IGR seems to be a suitable natural compound for development of new anti-inflammatory ingredient.